Regional comparative advantage and competitiveness of Malaysian palm oil products - Hassanpour, Behrooz; Ismail, Mohd Mansor (Malaysian Palm Oil Board, 2010)
This paper examines the competitiveness of the Malaysian industrial plantation commodities such as palm oil, cocoa, coconut and tea in selected ASEAN markets (Indonesia, Philippines, Singapore and Thailand) and China by using the Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) indices. The export data for seven groups of commodities based on the standard commodity categories as defined in the Harmonized Tariff System (HTS) at the 4-digit level were employed. The results indicate that Malaysia has competitive advantage in six commodities namely pepper (HS 0904), palm oil (HS 1511), coconut (copra) and palm kernel oil (HS 1513), cocoa paste (HS 1803), cocoa butter (HS 1804) and cocoa powder (HS 1805) but competitive disadvantage in one commodity, that is, tea (HS 0902). On the whole, based on the RCA rankings, Malaysia ranked first in three commodities (cocoa paste, cocoa butter and cocoa powder), Indonesia ranked first in three other commodities (tea, pepper and palm oil) while Philippine ranked first in coconut (copra).